An overview of the current state of women's leadership in higher education in Saudi Arabia and a proposal for future research directions - Azzah Alsubaie; Karen Jones (Administrative Sciences, 2017)
Despite the predominance of perspectives on women's leadership, which consistently emphasize the underrepresentation of women in virtually every sphere of political and economic life in countries around the world, very little is known about women's leadership, especially in higher education, in the Kingdom of Saudi Arabia (KSA). This has resulted in a gap in the literature, since higher education is one area of employment where Saudi women have made progress, and in spite of complex social, religious, cultural and organisational barriers, some have broken through the glass ceiling into higher education leadership. One goal of this paper is to highlight, through a synthesis of existing literature, the current state of women's higher education leadership in Saudi Arabia. The second goal of this paper is to propose new directions for future research to address the current dearth of empirical work on women's leadership in higher education in Saudi Arabia. This may be relevant to other regions of the Middle East and elsewhere.
Keywords: 350; Saudi Arabia; women; higher education; leadership research